Controlling 212Bi to 212Pb activity concentration ratio in thoron chambers. (November 2017) - He, Zhengzhong; Xiao, Detao; Lv, Lidan; Zhou, Qingzhi; Shan, Jian; Qiu, Shoukang; Wu, Xijun
Abstract: It is necessary to establish a reference atmosphere in a thoron chamber containing various ratios of 212 Bi to 212 Pb activity concentrations (C( 212 Bi)/C( 212 Pb)) to simulate typical environmental conditions (e.g., indoor or underground atmospheres). In this study, a novel method was developed for establishing and controlling C( 212 Bi)/C( 212 Pb) in a thoron chamber system based on an aging chamber and air recirculation loops which alter the ventilation rate. The effects of main factors on the C( 212 Bi)/C( 212 Pb) were explored, and a steady-state theoretical model was derived to calculate the ratio. The results show that the C( 212 Bi)/C( 212 Pb) inside the chamber is mainly dependent on ventilation rate. Ratios ranging from 0.33 to 0.83 are available under various ventilation. The stability coefficient of the ratios is better than 7%. The experimental results are close to the theoretical calculated results, which indicates that the model can serve as a guideline for the quantitative control of C( 212 Bi)/C( 212 Pb). Highlights: A novel method was developed for controlling C( 212 Bi)/C( 212 Pb) in thoron chambers. A theoretical model was derived for calculating C( 212 Bi)/C( 212 Pb). The coefficient of variation for C( 212 Bi)/C( 212 Pb) stability was less than 7%. Effects of main factors on C( 212 Bi)/C( 212 Pb) were explored. Various C( 212 Bi)/C( 212 Pb) were easily controlled.